PENGARUH SUHU PENYIMPANAN DAN PROPORSI TEH HIJAU: BUBUK DAUN KERING STEVIA (Stevia rebaudiana) TERHADAP AKTIVITAS ANTIOKSIDAN MINUMAN TEH HIJAU STEVIA DALAM KEMASAN BOTOL PLASTIK - Tristanto, Nerissa Arviana; Budianta, Dwi Wibawa; Utomo, Adrianus Rulianto (Widya Mandala Surabaya Catholic University, 2017)
Tea is a product that is often consumed with hot brewed and drink with the addition of sugar. Aternative substitution for sucrose is stevia sweetener. Green tea stevia beverages will be packaged in PET plastic into ready to drink products. This research is done to determine the effect of storage temperature and proportion of green tea: stevia dried leaf powder (Stevia rebaudiana) on antioxidant activity of green tea stevia beverage in plastic bottle packaging. The design of the study is a Randomized Block Design (RBD) factorial design with two factors. Factors that will be examined are differences in proportion of green tea stevia dried leaves powder which consist of five levels (100:0, 92:8, 84:16, 76:24, and 68:32 (w/w) in one gram sample) and storage temperature consists of two levels (refrigerator temperature (4-5Â°C) and room temperature (25-27Â°C)). The result showed that there where difference effect of total phenol, total flavonoid, DPPH free radical scavenging activity, iron ion reducing power on green tea stevia beverage. Total phenols, total flavonoids, iron ion reducing power, and DPPH Free Radical Scavenging Activity are 70.24-130.60 mg GAE/100 ml; 10.28-14.25 mg CE/100 ml; 27.38-95.24 mg GAE/100 ml; and 77.73-91.99 %. Total phenols, total flavonoids, iron ion reducing power, and DPPH Free Radical Scavenging Activity during storage at room temperature are 6.9759.71 mg GAE/100 ml; 2.71-10.44 mg CE/100 ml; 2.09-37.91 mg GAE/100 ml; and 38-65.84 %. Total phenols, total flavonoids, iron ion reducing power, and DPPH Free Radical Scavenging Activity during storage at refrigerator temperature are 28.13-104.13 mg GAE/100 ml; 4.95-42.56 mg CE/100 ml; 2.09-37.91 mg GAE/100 ml; and 42.52-70.63 %.